2018
DOI: 10.1016/j.agee.2018.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Rubber plantation ageing controls soil biodiversity after land conversion from cassava

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 57 publications
5
14
0
Order By: Relevance
“…In this regard, a previous study of ours (Abe et al Unpublished data) revealed that the soil organic C stock at the study site was maintained on a relatively constant level over the economic lifetime of rubber trees. Similar results have been documented elsewhere as follows: N'Dri et al (2018) found similar or even higher contents of soil organic C and total N in 25-year-old rubber gardens, compared with those at 7-year-old gardens in Cote d'Ivoire, and Peerawat et al (2018) reported no significant change in the contents of organic C, available P, exchangeable Ca, Mg, and K, and cation exchange capacity over the rubber's economic lifetime in eastern Thailand. In practice, soil organic matter management is often identified as a key practice in soil fertility maintenance in the smallholder farming system in tropical regions (Coleman et al 1989), although the rubber farmers in our study site have no specific strategy for managing the soil organic matter for the moment.…”
Section: Fig 1 Changes In the Soil Properties In Relation To The Desupporting
confidence: 90%
See 1 more Smart Citation
“…In this regard, a previous study of ours (Abe et al Unpublished data) revealed that the soil organic C stock at the study site was maintained on a relatively constant level over the economic lifetime of rubber trees. Similar results have been documented elsewhere as follows: N'Dri et al (2018) found similar or even higher contents of soil organic C and total N in 25-year-old rubber gardens, compared with those at 7-year-old gardens in Cote d'Ivoire, and Peerawat et al (2018) reported no significant change in the contents of organic C, available P, exchangeable Ca, Mg, and K, and cation exchange capacity over the rubber's economic lifetime in eastern Thailand. In practice, soil organic matter management is often identified as a key practice in soil fertility maintenance in the smallholder farming system in tropical regions (Coleman et al 1989), although the rubber farmers in our study site have no specific strategy for managing the soil organic matter for the moment.…”
Section: Fig 1 Changes In the Soil Properties In Relation To The Desupporting
confidence: 90%
“…In fact, many previous studies reported the depletion of soil organic matter and mineral nutrients by land use change from primary or secondary forests to rubber plantation (e.g., Li et al 2012, de Blécourt et al 2013, Kotowska et al 2015, Allen et al 2015, and the soil degradation in rubber gardens can also increase with an increase in the age of the rubber tree stand (e.g., Aweto 1987, 2001, Cheng et al 2007. In contrast, other reports delivered inconsistent results to those previously documented: the soil fertility under rubber farming was similar to that under primary and secondary forests (e.g., Tanaka et al 2009, Moreira et al 2013, and little loss or even enhanced content of organic matter and some nutrients in the soil were found during rubber cultivation (Guillaume et al 2016, N'Dri et al 2018, Peerawat et al 2018. These contradictory findings warrant further research on the changes in soil fertility caused by rubber plantation.…”
Section: Introductionmentioning
confidence: 96%
“…Correspondingly, we found a higher abundance of carbon and nitrogen in organically managed soils, and higher phosphorus in conventionally-managed soils, in accordance with other studies of coffee agroecosystems in other countries (Partelli et al 2012). Differences in soil carbon, phosphorus, and nitrogen are strong determinants of bacterial community composition The previous land use of each farm had a strong effect on the soil microbiome, consistent with experimental findings of legacy effects on the assembly of soil microbial communities (Jurburg et al 2017;Peerawat et al 2018;Turley et al 2020). Our study further shows the persistent effect of previous land uses on lands under active cultivation.…”
Section: Discussionsupporting
confidence: 91%
“…The tillage layer thickness is often used as an important indicator to judge land degradation for farmers. The soil is a non-renewable resource with ecological functions to maintain and improve soil and water conservation [30,31]. The core of cultivated land quality is soil quality.…”
Section: Construction Of Cultivated Land Evaluation Systemmentioning
confidence: 99%